Overlap syndrome of atopic dermatitis and allergic contact dermatitis: metabolic patterns - L.V. Konovalenko; V.I. Litus; Yu.I. Komisarenko; O.I. Litus (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. In recent years, multifaceted studies of the relationship between allergic skin diseases, in particular atopic dermatitis (AD) and allergic contact dermatitis (ACD), and metabolic disorders have been actively developing. Studies have shown that type 2 diabetes mellitus can increase the risk of AD. Inflammation and oxidative stress, which are observed in metabolic syndrome, have been inextricably linked to ACD, since reactive oxygen species are involved in the initial sensitization to the allergen, as well as in the development of pathogenic allergic reactions. The purpose of the study was to investigate the clinical efficacy of treatment for AD and ACD overlap syndrome (OS) in patients with metabolic disorders. Materials and methods. Comprehensive treatment of patients with AD and ACD OS who had impaired glycemia and lipid metabolism was performed. Before the start of treatment, after a month and 3 months, a lipid profile, fasting glucose and glycated hemoglobin (HbA1c) indicators were evaluated. Patients were also assessed for the prevalence of eczema using the Eczema Area and Severity Index (EASI). Results. After the treatment, patients showed a tendency to reduce blood glucose (from 6.80 ± 0.18 to 5.20 ± 0.11 mmol) and HbA1c (from 6.40 ± 0.22 to 5.10 ± 0.16 %) from 1 to 3 months of observation, and lipid profile indicators normalized: the concentration of total cholesterol, triglycerides, low-density lipoproteins decreased, while high-density lipoproteins showed a tendency to increase. The assessment of the prevalence of eczema according to the EASI showed that before the start of treatment, mild lesions were present in 11 (25.0 %) patients, moderate — in 17 (38.6 %), and the proportion of patients with severe and widespread lesions was 18.2 %. At the end of the monitoring period, 20 (45.5 %) patients had no obvious clinical manifestations of the disease, 20 (45.5 %) patients had mild form, 6 (13.6 %) had moderate, and 4.6 % had severe and widespread lesions. Conclusions. The proposed algorithm for the management of patients with AD and ACD OS who have metabolic syndrome and prediabetes is effective, as evidenced by the obtained data on glycemic indicators and lipid profiles in dynamics, as well as the results of the assessment on the EASI.